Thermal performance improvement of forced-air cooling system combined with liquid spray for densely packed batteries of electric vehicle - Dhuchakallaya, Isares; Saechan,, Patcharin; Mohd Sa'at, Fatimah Al Zahrah (Engineered Science Publisher, 2023)
In the electric vehicles (EVs), battery thermal management system (BTMS) serves a key role in addressing the issue of excessive heat generated from chemical reactions and internal resistance which can cause capacity fade, thermal runaway and instability issues. In this study, a novel cooling system that combines liquid spray and forced-air is proposed. The cooling fluid used is Hydrofluoroether (HFE) which is a non-electrically conductive liquid. The study develops a transient heat transfer model of the battery module and investigates the effects of injection rate and injector arrangement on cooling performance. The results demonstrate that increasing the amount of HFE can further decrease the maximum temperature and the temperature non-uniformity of the battery module, but cost benefit considerations must be taken into account. The injector layout also has a significant impact on the temperature distribution of the module. Optimizing the cooling system can reduce the maximum temperature and temperature difference of the module by 5.9 °C and 4.0 °C, respectively, compared to dry air cooling. These findings of the spray-assisted forced-air cooling system provide useful insights for developing a practical thermal management solution for EVs.